Dikdea Skrining Risiko Diabetes Melitus pada Remaja - Uni Afriyanti; Muhammad Ra’uf; Yosra Sigit Pramono; Candra Kusuma Negara; Ricky Prawira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the effectiveness of Dikdea as a Diabetes Mellitus risk screening tool for adolescents. The study employed a quantitative research design using a Randomized Controlled Trial (RCT) with a pretest–posttest control group design. The results showed that the intervention group experienced significant improvements in knowledge, attitudes, and healthy behaviors related to Diabetes Mellitus prevention compared to the control group, with significant differences in knowledge (p=0.021), attitudes (p=0.017), and healthy behaviors (p=0.013). Receiver Operating Characteristic (ROC) analysis also showed that Dikdea had good diagnostic ability (AUC=0.87; sensitivity 84.2%; specificity 79.5%). In conclusion, Dikdea is an effective non-invasive screening tool for identifying the risk of Diabetes Mellitus among adolescents and has the potential to be implemented as a school-based screening strategy to support the early detection and prevention of Diabetes Mellitus. Keywords: Adolescents, Diabetes Mellitus, Early Detection, Risk Screening